Strategi Peningkatan Kredibilitas Asesor BAN-S/M guna Meningkatan Mutu Pendidikan Islam - Faojin, Mohamad; Lubis , Muhammad Sihabudin (Lembaga Penelitian Dan Pengabdian Masyarakat Stai Brebes, 2023)
In an effort to oversee the credibility of the assessor in carrying out their duties, BAN-S/M conducts an assessment by spreading the instruments used by members of BAN-S/M at the time of monitoring and evaluation (Monev). The assessors who did not carry out their duties in accordance with the instructions and the code of ethics were given punishment without being involved in carrying out accreditation the following year. Results and accreditation reports to be detailed to operational aspects in the form of systematic analysis of the recommendations of each component analyzed according to the instrument used, as well as a clear recommendation about the follow-up that should be carried out by stakeholders at the education unit level in order to fix in future to improve the quality of education and status or ranking of accreditation